Development of Controlling in Postindustrial Economy: Tools and Techniques - Klochko, Elena Nikolaevna; Rybyantseva, Maria Sergeevna; Oksanich, Elena Anatolevna (International Journal of Economics and Financial Issues, 2016)
This article highlights the development of controlling in a historical retrospective. The periodization of controlling allocates two basic steps: 1accounting primitiveness (the priority control function of accounting, primary documents are financial statements); 2 accounting differentiation (emergence of double-entry accounting, complexity of the methodology, the emergence of information function and the science of accounting). The attention is paid to a contribution of national accounting schools (Italian, French, German, Anglo-American, Russian) to the formation and development of controlling. The main instruments of expeditious and strategic controlling are considered. Tools are considered in a section of management accounting and the administrative analysis. The attention is also paid to the indicator systems within the controlling. At application of not projective method, there is a search of the necessary decision thanks to overcoming the psychological inertia consisting in aspiration to solve a problem in the traditional way. Keywords: strategic controlling, management accounting, administrative analysis JEL Classifications: B15; M41; M3